Analysis of Technical Operational Failures Risk in TPS 3R Using Failure Mode and Effects Analysis (FMEA) - Faqih Mustafiq; I Made Wahyu Widyarsana (Jurnal Serambi Engineering, 2026)
Waste management in Indonesia continues to face operational challenges due to the predominance of the collect–transport–dispose approach, which limits waste reduction efforts at the source. This study aims to identify and prioritize technical operational failure risks in community-based waste management facilities (TPS 3R) located at TPS 3R Mutiara Bogor Raya, TPS 3R Ciparigi 2, and TPS 3R Jalan Jawa, Bogor City, Indonesia. Data were collected through field observations, semi-structured interviews with facility managers, and community questionnaires regarding waste storage and source segregation practices. Risk assessment was conducted using the Failure Modes and Effects Analysis (FMEA) method by evaluating Severity, Occurrence, and Detection parameters to obtain Risk Priority Number (RPN) values. The results indicate that operational failure risks are primarily associated with managerial capacity, waste storage and segregation systems, collection operations, and waste processing activities. The highest priority risks include failure of operational management systems (RPN 64) and unreliable waste processing chains (RPN 60) at TPS 3R Mutiara Bogor Raya, inadequate collection route planning (RPN 48) at TPS 3R Ciparigi 2, and unequal fleet distribution (RPN 48) at TPS 3R Jalan Jawa. Overall, low source segregation participation and operational system limitations were identified as dominant factors influencing TPS 3R performance. Strengthening management systems, operational planning, and community participation is therefore essential to improve facility sustainability.